1. The problem statement, all variables and given/known data Let f(x) = 2x^3 + 5x + 3 Find the inverse at f^-1(x) = 1 2. Relevant equations N/A 3. The attempt at a solution The only way that I know how to solve inverses is by solving for X, then replacing it by Y. Then I supposed I would sub 1 into the inverted polynomial. However I'm not sure how to solve for X. My attempt: y - 3 = 2x^3 + 5x (y - 3)/x = x(2x^2 + 5) Then, hopelessness. Any info will be extremely helpful for my test this Friday. Thank you.